2006
DOI: 10.1002/ijc.21878
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NSAIDs on the recurrence of nonmelanoma skin cancer

Abstract: Experimental studies have consistently shown a protective effect of nonsteroidal antiinflammatory drugs (NSAIDs) against nonmelanoma skin cancers (NMSC). However, little human epidemiological research has been done in this regard. We used data from the Skin Cancer Chemoprevention Study to explore the association of NSAID use and with the risk of basal-cell carcinoma (BCC) and squamous-cell carcinoma (SCC). 1,805 subjects with a recent history of NMSC were randomized to placebo or 50 mg of daily b-cartene. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
43
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 56 publications
(69 reference statements)
4
43
0
Order By: Relevance
“…On average, previous studies reported a higher prevalence of NSAID use. [3][4][5][6][7][8][9][10][11][12][13] This discrepancy is likely attributable to differences in defining ''ever users,'' age and sex distributions, and the source of exposure data (self-reported vs prescription records).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On average, previous studies reported a higher prevalence of NSAID use. [3][4][5][6][7][8][9][10][11][12][13] This discrepancy is likely attributable to differences in defining ''ever users,'' age and sex distributions, and the source of exposure data (self-reported vs prescription records).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Previous studies largely support a protective role of NSAIDs in development of keratinocyte carcinomas, ie, squamous cell carcinoma (SCC) and basal cell carcinoma (BCC), as well as malignant melanoma (MM). [3][4][5][6][7][8][9][10][11][12][13] Thus, the results from 1 randomized controlled study indicated a lower risk of keratinocyte carcinomas associated with use of the COX-2 inhibitor celecoxib. 8 However, the previous studies are controversial and are difficult to compare because of differences in outcome measures (eg, inclusion or exclusion of in situ cancers), study design, study populations (eg, high-risk populations vs general populations), and type and measure of NSAID use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11) and their potential to increase the risk of UVR-related skin cancers, very few epidemiologic studies have addressed the question of a possible association of photosensitizing medication use with skin cancer (4,(12)(13)(14), and the results of these studies have often been equivocal. Furthermore, skin cancers are not a single entity but different diseases with different sun exposure-related risk factors; for example, early, intermittent overexposure to the sun is thought to be most important for the development of CMM and basal cell carcinoma (BCC; refs.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of sporadic BCCs with topical retinoids such as tazarotene can be successful; however complete tumor regression occurs in less than 50% of BCCs so treated (Bianchi et al, 2004). A retinoid precursor, β-carotene, and other less toxic agents such as non-steroidal anti-inflammatory agents (NSAIDs), do not have a significant effect in lowering BCC risk (Frieling et al, 2000) (Grau et al, 2006). One provocative study has suggested that BCC may also be prevented with a low-fat diet.…”
mentioning
confidence: 99%